2002
DOI: 10.1021/la0267037
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Structures of Glycine on Cu(111)

Abstract: Adsorption and self-assembly of glycine on the Cu(111) surface are studied by means of scanning tunneling microscopy in an ultrahigh vacuum environment. The results show that the adsorbates are chemisorbed on the surface, may take three different conformations, and can form the 2-D gas phase, the chain phase, and two superstructures (2-D solid phases). Although the chain phase was reported as seen from several other amino acid/Cu(001) systems, a concrete model of it is proposed here for the first time. Besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 27 publications
6
66
1
Order By: Relevance
“…The calculations also indicate that the heterochiral (3×2) adlayer is more stable than the homochiral (3×2) one: the predicted adsorption energy is -2.82 eV for the former and -2.76 eV for the latter. This results indicated that large regions of the homochiral (3×2) glycine adlayer are unlikely to exist on Cu (110), in agreement with the conclusions of refs. [66; 173] .…”
Section: Glycine Adsorption At Cu Surfacessupporting
confidence: 92%
See 3 more Smart Citations
“…The calculations also indicate that the heterochiral (3×2) adlayer is more stable than the homochiral (3×2) one: the predicted adsorption energy is -2.82 eV for the former and -2.76 eV for the latter. This results indicated that large regions of the homochiral (3×2) glycine adlayer are unlikely to exist on Cu (110), in agreement with the conclusions of refs. [66; 173] .…”
Section: Glycine Adsorption At Cu Surfacessupporting
confidence: 92%
“…The centred (3×2) structure with two molecules per unit cell results from a compromise between optimal adsorbate site, intermolecular hydrogen bonding and maximum adsorbate density. The threefold and twofold periodicities along the <-110> and <001> directions, respectively, lead to an almost square unit cell; this structure is quite common for small -amino acids on Cu (110), since the molecules are bound to the surface through the AA functional groups and let the radical tail protrude far from the surface. The corresponding STM analysis of the (3×2)g-Gly/Cu(110) overlayer showed both homochiral and heterochiral domains at the surface [101].…”
Section: Glycine Adsorption At Cu Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…In all three of these cases, the acid is deprotonated by interaction with the Cu surface to form, respectively, glycinate (NH 2 CH 2 COO) and alaninate (NH 2 CH 3 CHCOO) species that bond to the surface through both of the carboxylate O atoms and the amino N atom, all three atoms occupying single-coordinated sites. This bonding configuration is consistent with a number of studies using electronic [7,8] and vibrational spectroscopy [9,10,11], and also scanning tunnelling microscopy [12,13,14,15,16,17] and density functional theory (DFT) calculations [18,19]. Some of these spectroscopic studies, however, do indicate that at different surface coverages, or in less well-ordered overlayers, other chemisorption bonding configurations probably occur involving only one or both of the carboxylate O atoms.…”
Section: Introductionsupporting
confidence: 86%